2017
DOI: 10.1097/scs.0000000000003976
|View full text |Cite
|
Sign up to set email alerts
|

Management of Peri-Implant Hypertrophic Scarring for an Ear Prosthesis

Abstract: The clinical report describes a case of a 14-year-old patient with a traumatic amputation of the left auricle and severe hypertrophic scarring. The management of peri-implant soft tissue was challenging, but successful in the rehabilitation of a patient with auricular prosthesis retained by implants. The prosthesis restored the patient's facial aesthetics and contributed not only to function, but also to psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…3 The most vulnerable sites are the shoulders, backs, chests, and earlobes with high tension. [5][6][7] Current treatments for hypertrophic scars and keloids include surgical excision, glucocorticoid injection, radiation therapy, and mesenchymal stem cells. 8 Meta-analysis revealed that surgery combined with radiotherapy had a lower recurrence rate than radiotherapy (22% vs 37%) in keloids.…”
Section: Brief Introduction Of Keloid and Hypertrophic Scarmentioning
confidence: 99%
“…3 The most vulnerable sites are the shoulders, backs, chests, and earlobes with high tension. [5][6][7] Current treatments for hypertrophic scars and keloids include surgical excision, glucocorticoid injection, radiation therapy, and mesenchymal stem cells. 8 Meta-analysis revealed that surgery combined with radiotherapy had a lower recurrence rate than radiotherapy (22% vs 37%) in keloids.…”
Section: Brief Introduction Of Keloid and Hypertrophic Scarmentioning
confidence: 99%